Challenges in radiocarbon dating organic carbon in opal-rich marine sediments - Zheng, Y.; Anderson, R. F.; Froelich, P. N.; Beck, W.; McNichol, A. P.; Guilderson, T. (Radiocarbon, 2002)
We explored the reliability of radiocarbon ages obtained on organic carbon phases in opal-rich Southern Ocean sediments. Paired biogenic carbonate and total organic carbon (TOC) C-14 analyses for three Southern Ocean cores showed that the TOC ages were systematically younger than the carbonate ages. Carbonate ages were consistent with oxygen isotopic and bio-stratigraphy, indicating error in TOC ages that could be explained by 5-24% of modern carbon contamination of TOC samples. Two possible sources of contamination are: 1) adsorption of atmospheric CO2 or volatile organic compounds to reactive opal surface sites, and 2) fixation of atmospheric CO2 by chemosynthetic bacteria during core storage. In an effort to reduce the modem carbon contamination, diatoms were separated from sediments, purified, and pre-oxidized by concentrated nitric and perchloric acids to permit dating of opal-intrinsic organic carbon (similar to0.1-0.3% by weight). C-14 ages of chemically pre-oxidized opal showed a significant amount of modem carbon contamination, from 11 to 32%, indicating adsorption from the atmosphere of modem carbon onto opal surfaces that were previously cleaned by acid oxidation. Several experiments designed to eliminate the modern C contamination were attempted, but so far we have not been able to obtain a radiocarbon age on C-14-dead Southern Ocean opal-rich sediments, either bulk TOC or purified diatom opal samples, as old as our procedural blank.
591keTimes Cited:13Cited References Count:28